AN INVESTIGATION OF LEARNING APPROACHES AND LANGUAGE LEARNING STRATEGIES: ARE THEY RELATED? - ERDOGAN, Tolga; OZDEMİR, Emrah (The Eurasia Proceedings of Educational and Social Sciences, 2017)
In related research, learning approaches and learning strategies have been reported as important variables influencing the quality of student learning. The aim of the present study is to investigate the relationship between the learning approaches and the language learning strategies of higher education students. The research was conducted with the participation of 493 freshmen (M=257, F=236) attending various departments at Balikesir University in Turkey. For research purposes, the Turkish versions of Strategy Inventory of Language Learning (SILL) and the Approaches and Study Skills Inventory for Students (ASSIST) were used. After the reliability of both instruments was computed, descriptive and inferential statistics were used to analyze data. The findings are to be discussed and commented considering students' levels of language learning strategy use and their learning approaches and changes in those levels according to participants' gender and field of study.